“ONE FOR ALL AND ALL FOR ONE": INTERORGANIZATIONAL RELATIONS ON ROUTE SALAMARIAS- RS - Siqueira Colet, Daniela; Universidade de Passo Fundo (2016)
This article aims to understand how to configure the interorganizational relations on Route Salamarias, identifying the possible gains from this cooperative relation. Therefore, there was an exploratory research, multicase type and qualitative approach to data analysis. The search field constitutes the route of Salamarias, productive cluster of small farms, located in the Marau city, north of state Rio Grande do Sul. The results evidence that the established interorganizational relations has brought satisfactory results to those involved, with intensive cooperation between them. The findings point to a mutual compromise between the participants, trust and transparency in relations, presenting as a case of productive successful cluster, which maintains intense interorganizational relations.